Administration of oral tranexamic acid is equally effective with intradermal injections in reducing the amount of melanin in female marmots (Cavia porcellus) exposed to ultraviolet-b - Ni Luh Putri Astini; Wimpie Pangkahila; AAGP Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2018)
Introduction: Oral studies of tranexamic acid significantly reduce the MASI (Melasma Area and Severity Index) value but have not evaluated a decrease in the amount of melanin. The purpose of this study is to prove that oral tranexamic acid can reduce the amount of melanin and have the same effectiveness as intradermal injections in female guinea pigs exposed to ultraviolet B. Method: A posttest only control group design study was conducted using 32 female mice, aged 6-8 weeks, weight 250-280 grams, which were randomly divided into 2 groups. Group 1 was given an intradermal injection of tranexamic acid 5 mg/ml, 0.5 ml/cm and exposure to UVB. Group 2 was given oral treatment of tranexamic acid 250 mg twice a day and exposure to UVB. The treatment was given for 4 weeks. Total UVB exposure was 390mj/sec. The study was conducted in the animal laboratory of the Udayana medical faculty. Results: The statistic result showed that the data were normally distributed and homogenous. The comparative test with the independent sample t-test indicated that there was no significant difference between intradermal injections with oral tranexamic acid administration in reducing the amount of melanin in female guinea pigs exposed to UVB with p> 0.05. Conclusion: oral tranexamic acid significantly reduced the amount of melanin and had the same effectiveness as intradermal injections in reducing the amount of melanin in female guinea pigs exposed to UVB.